Heat transfer analysis of CNT suspended nanofluid through annulus sector duct. (March 2017) - Ahmed, Farhan; Akbar, Noreen Sher
Abstract: In this paper, we have numerically analysed the effects of single and multi-walled carbon nanotubes on the base fluid water through the vertical annulus sector duct, under the influence of Buoyancy force. A discretized form of governing dimensionless momentum and energy equation obtain with the help of finite volume based method and uses strongly implicit procedure (SIP) to solve the algebraic system. It has been observed that volume fraction of carbon nanotubes has direct relationship with the heat transfer coefficient and friction factor. Furthermore, limiting case results obtained in this study, are comparable with the published data in the absence of carbon nanotubes and Buoyancy force. Highlights: Nanofluid flow synthesized for through annulus sector duct. Nano Phase Model is presented. Buoyancy effects are also taken into account. Mixed Convective Flow is employed. Comparative study for different article is conducted.